Compliant and Robust Tissue‐Like Hydrogels via Ferric Ion‐Induced of Hierarchical Structure. (8th January 2023) - Wang, Yi; Xie, Yuanjie; Xie, Xiangyan; Wu, Di; Wu, Haitao; Luo, Xingqi; Wu, Qi; Zhao, Lijuan; Wu, Jinrong
Abstract: It is a challenge to synthesize materials that possess biological tissue‐like properties: strain‐stiffening, robust yet compliant, sensitive, and water‐rich. Herein,  a ferric ion‐induced salting out and coordination cross‐linking strategy is presented to create a hierarchical hydrogel network, including dipole–dipole interactions connected curved chains, acrylonitrile (AN)‐rich clusters, and homogeneous iron‐ligand interactions. The design allows the network to deform stress‐free under small strain by unfolding the curved segments with the elastic deformation of the AN‐rich clusters, and sequentially breaking the dipole–dipole interactions and iron‐ligand interactions from weak to strong ones under large strain. As a result, the hydrogel exhibits tissue‐like mechanical properties: low elastic modulus (0.06 MPa), high strength (1.4 MPa), high toughness (5.1 MJ m −3 ), intense strain‐stiffening capability (27.5 folds of stiffness enhancement), excellent self‐recovery ability and fatigue resistance. Moreover, the hydrogel exhibits high water content (≈84%), good biocompatibility and multi‐sensory capabilities to strain, pressure and hazardous chemicals stimuli. Therefore, this work offers a novel strategy to prepare hydrogel that can mimic the diverse functions of tissues, thereby expanding advanced applications of hydrogel in soft robotics, wearable devices, and biomedical engineering. Abstract : This work reports a ferric ion‐induced salting out and coordination cross‐linking strategy to create a hierarchical and dynamic hydrogel network, which can mimic the diverse functions of tissues. As a result, the hydrogel possesses tissue‐like combinational properties: superior compliance, high toughness, immense strain‐stiffening, outstanding self‐recovery property, excellent fatigue resistance, high water content, good biocompatibility, and multi‐sensory capabilities.